Transcutaneous Electrical Nerve Stimulation Therapy in Temporomandibular Disorder: A Clinical Study - Ganapathi Moger; M C Shashikanth; M K Sunil; P Shambulingappa (Wolters Kluwer Medknow Publications, 2011)
Aims: Though use of transcutaneous electrical nerve stimulation (TENS) in dentistry was first described in 1967 by Shane and Kessler, it has yet to gain widespread acceptance in dentistry. This study was designed to evaluate and compare the effectiveness of active and placebo TENS therapies in the treatment of temporomandibular disorder. Methods: Thirty patients received active TENS therapy and 15 received placebo TENS therapy. VAS was used to measure changes in pain and tenderness in the muscles of mastication and TMJS during and after therapy- Also, changes in mouth opening was recorded and analyzed. Results: A significant improvement was observed in both active and placebo TENS therapies regarding orofacial pain, muscles and TMJs tenderness and interincisal distance. None of the parameters except medial pterygoid muscle tenderness revealed any differences between the methods. Conclusion: This study justifies the use of TENS therapy as well as placebo in the management of TMD. TENS therapy appears to be useful in relieving pain, especially muscular and chronic pain Hence, along with TENS therapy, placebo should also be considered as a potent and independent therapeutic modality in its own right.